2014
DOI: 10.1039/c4cc07273a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of proton conductivity in graphene oxide by filling sulfate ions

Abstract: Graphene oxide (GO) walled channels filled by sulfate ions exhibit an optimized proton conductivity, which is higher than the proton conductivity of all other forms of GO. The sulphate ion increases the water absorbing capacity and hydrogen bond reformation process in GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 21 publications
7
107
0
Order By: Relevance
“…For instance, increasing the PGO content from 0.5% to 2.5% elevates the proton conductivity from 19.0 to 31.0 mS cm -1 . Though the imbedding of GO also promotes the proton conduction of nanohybrid membranes due to the generation of acid-base pairs between carboxylic acid group from GO and amino group from CS and the contribution of epoxide groups on GO surface to proton transport [53], the enhancement effect is weaker than that of PGO due to the absence of PA groups.…”
Section: Water Uptake Area Swelling and Iec Of The Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, increasing the PGO content from 0.5% to 2.5% elevates the proton conductivity from 19.0 to 31.0 mS cm -1 . Though the imbedding of GO also promotes the proton conduction of nanohybrid membranes due to the generation of acid-base pairs between carboxylic acid group from GO and amino group from CS and the contribution of epoxide groups on GO surface to proton transport [53], the enhancement effect is weaker than that of PGO due to the absence of PA groups.…”
Section: Water Uptake Area Swelling and Iec Of The Membranesmentioning
confidence: 99%
“…, the spectrum of GO exhibits the C 1s band and O 1s band at 286.86 and 532.67 eV, respectively[45,46], and the GO is consisted of 59.2% C and 40.8% O. After surface phosphorylation, the spectrum of PGO gives rise to the P 2p bands at 133.24 eV (P-O bonding) and 133.88 eV (P-C bonding).…”
mentioning
confidence: 98%
“…After oxidation, all the samples exhibit two individual peaks near 285 and 287 eV in their XPS spectra [36][37][38]. The deconvolution of spectra shows that GO exhibits characteristic peaks comprising several particular oxygenated functional groups.…”
Section: Monitoring the Graphite → Go → G Conversion And Characterizamentioning
confidence: 99%
“…Endeavours have been made to study GO 3,4 and have found that the oxygencontaining functional groups from GO can not only donate protons but also transfer protons [5][6][7] . Besides directly using GO as PEMs fillers, incorporating functionalized GO into PEM matrix has been reported as well 6,[8][9][10][11][12][13][14] . Chen et al 6 sulfonated GO and found the S-GO/Nafion composite membrane showed significant improvement in proton conductivity at 25% relative humidity (RH).…”
mentioning
confidence: 99%